Mobile psychiatry: Personalised Ambient Monitoring for the mentally ill - Prociów, Paweł (2011)
Mental health has long been a neglected problem in global healthcare. The social and economic impacts of conditions affecting the mind are still underestimated. However, in recent years it is becoming more apparent that mental disorders are a growing global concern that is not to be trivialised. Considering the rising burden of psychiatric illnesses, there is a necessity of developing novel services and researching effective means of providing interventions to sufferers. Such novel services could include technology-based solutions already used in other healthcare applications but are yet to make their way into standard psychiatric practice.